HRI London 2023: The Homeopathy Research Community Reunites after a 4-Year Hiatus, Sparking Fresh Collaborations between Researchers ‘Old and New’ - Roberts, E. Rachel; Mosley, Angelina J.; van der Werf, Esther T.; Tournier, Alexander L. (Homeopathy, 2024)
The Homeopathy Research Institute's (HRI) 5th international research conference took place in the heart of London, from 16th to 18th June 2023. With 230 attendees from 27 countries, HRI's conferences remain truly international. HRI London 2023 will be remembered for its inspiring blend of ‘old and new’, with a programme notable for the maturity of the evidence presented by experienced names drawing on decades of work, as well as the enthusiasm and skill of up-and-coming researchers who took the floor to present their new findings. In this report, we present scientific highlights from the event.
Keywords: homeopathy research; conference; aquaculture; clinical trials; agrohomeopathy; fundamental research